Extralobar pulmonary sequestrations hiding congenital diaphragmatic defects: A case series - Negri, Elisa; Cantone, Noemi; Severi, Elisa; Belli, Gilda; Tocchioni, Francesca; Centonze, Nicola; Ciardini, Enrico; Noccioli, Bruno (Journal of Neonatal Surgery, 2021)
Background: Association between pulmonary sequestration and diaphragmatic hernia is well known. Extralobar sequestrations are masses of the non-functioning lung, surrounded by separate pleura, without bronchial communication, and with a systemic arterial blood supply. They may be placed in the thorax, within the diaphragm, or rarely in a sub-diaphragmatic position. Case Series: We present three cases of extra-lobar extra-thoracic pulmonary sequestrations associated with different types of diaphragmatic defects. In none of the three cases, the diaphragmatic defect was detected prenatally. Conclusion: Pulmonary sequestration may be involved in the embryological origin of the diaphragmatic defect. Simultaneously, it acts as an anatomical barrier and prevents the herniation of the abdominal content into the thorax. If extralobar pulmonary sequestration is diagnosed prenatally, a coexistent diaphragmatic hernia should always be considered.